Subcutaneous Implantable Defibrillator programming: an analysis of Italian clinical practice and its evolution. (3rd October 2022) - Rordorf, R; Viani, S; Biffi, M; Pieragnoli, P; Nigro, G; Migliore, F; Francia, P; De Filippo, P; Dello Russo, A; D'Onofrio, A; Bisignani, G; Ottaviano, L; et al.
Abstract: Background: The UNTOUCHED study (designed in 2017 and published in 2021) demonstrated high success rate for termination of ventricular arrhythmias, and very low inappropriate shock rate in subcutaneous implantable cardioverter-defibrillator (S-ICD) recipients. The prescribed device programming included a conditional zone between 200 and 250 beats per minute (bpm) with discrimination algorithms employed to avoid delivering inappropriate shocks in this range, and a shock zone based on the rate alone for arrhythmias >250 bpm. Whether these results influenced clinical practice is unknown. Methods: We assessed the programming at implantation and changes in programmed parameters at follow-up (≥1 year) in a cohort of S-ICD recipients enrolled in the Rhythm Detect registry at 56 centers. Results: From 2013 to 2021, 1521 consecutive patients (aged 49±15 years; 79% male, 52% dilated cardiomyopathy, 31% arrhythmic syndromes, 16% hypertrophic cardiomyopathy) were analyzed. At implantation, the programmed sensing vector was the Primary in 59% of patients, the Secondary in 35%, the Alternate in 6%. At follow-up, the sensed vector was changed in 13% of patients. The programmed conditional zone cutoff was set to 200 [200–220] bpm (median [25–75 percentile]), and the shock zone cutoff to 230 [210–250] bpm. At follow-up, the conditional zone cutoff was reprogrammed in 13% of patients, but the median value in the overall population did not change (200 [200–220] bpm; p>0.05). The shock zone cutoff was reprogrammed in 43% of cases, and the overall median value was 250 [230–250] bpm (p<0.001 versus implantation). Sorting patients by implantation date, we observed that in the first 764 patients (implanted ≤2017) the shock zone cutoff was set to 210 [210–230] bpm at implantation and to 240 [230–250] bpm at follow-up (reprogrammed in 66% of cases). While in patients implanted >2017, it was already set to 250 [230–250] bpm at implantation and to 250 [240–250] bpm at follow-up (reprogrammed in 20% of cases, p<0.001 versus ≤2017). Conclusions: S-ICD programming parameters are rarely changed during follow-up (approximately 13% of patients). The only exception in clinical practice was the shock zone cutoff. Centers have begun to program high cutoffs in recent years. This happened at the time of implantation for new S-ICD recipients and at follow-up for pre-existing implants. This behavior is consistent with a substantial adoption of published trial findings and could contribute to reduce the incidence of inappropriate shocks in clinical practice. Funding Acknowledgement: Type of funding sources: None.